Acute upper airway obstruction due to retropharyngeal hematoma in a dog with Anaplasma species: a case study. Issue 1 (December 2015) - Vieitez, Verónica; Martín-Cuervo, María; López-Ramis, Víctor; Ezquerra, Luis
Abstract Background Retropharyngeal hematoma is a rare condition that is difficult to diagnose and may progress rapidly to airway obstruction. The authors report the first known case of acute upper airway obstruction resulting from retropharyngeal hematoma in a dog. Documented causes in human medicine have included coagulopathic states, trauma, infection, parathyroid adenoma rupture, and foreign body ingestion. Vague symptoms in humans such as sore throat, shortness of breath, dysphonia, dysphagia, and neck swelling may precede lethal airway obstruction. Case presentation The authors report a case of an 18-month-old, intact female water spaniel with thrombocytopenia that developed a massive retropharyngeal hematoma and symptoms of airway compromise. The dog required tracheal intubation followed by surgical tracheostomy. Lateral cervical radiography and magnetic resonance imaging of the neck was consistent with a retropharyngeal hematoma compromising the airway. The retropharyngeal hematoma was managed conservatively. Conclusion Retropharyngeal hematoma should be considered in patients presenting with abrupt respiratory distress. Magnetic resonance imaging allowed specific diagnosis of a rare condition that is otherwise difficult to diagnose.